2007
DOI: 10.1111/j.1745-4522.2007.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Fatty Acid Content of Buffalo Cheese From Northwest Argentina: Effect on Lipid Composition of Mice Tissues

Abstract: Chemical properties, long chain fatty acid composition and conjugated linoleic acid (CLA) content of buffalo cheese were determined. Good nutritional properties were observed in cheese, showing 11.5% of protein, 18.3% of fat and 30.5% of dry matter. Saturated fatty acid content was 65.6%, monounsaturated fatty acid was 31.8% and polyunsaturated was 2.6%. Stearic (C16:0) and oleic (C18:1) acids were the major fatty acids (FAs) present in milk and cheese. Values slightly higher of CLA were determined in cheese (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
2
5
0
4
Order By: Relevance
“…SFA with the highest percentages were palmitic (16:0), stearic (18:0) and myristic (14:0). Similar results were reported by Van Nieuwenhove et al (2007) for Argentinean crossbred (Murrah × Mediterranean breeds) milking buffaloes on ad-libitum intake of natural pasture.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…SFA with the highest percentages were palmitic (16:0), stearic (18:0) and myristic (14:0). Similar results were reported by Van Nieuwenhove et al (2007) for Argentinean crossbred (Murrah × Mediterranean breeds) milking buffaloes on ad-libitum intake of natural pasture.…”
Section: Resultssupporting
confidence: 90%
“…Proportions of saturated (SFA) and unsaturated (UFA) fatty acids were 62·89% and 33·97%, respectively (Table 1). For buffalo raw milk, Van Nieuwenhove et al (2007) reported similar SFA and UFA values, 65·9% and 34·1%, respectively. SFA with the highest percentages were palmitic (16:0), stearic (18:0) and myristic (14:0).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…O valor médio de pH encontrado no Requeijão Marajoara tipo creme foi de 5,15, sendo menor que os determinados por LOURENÇO (1999) VAN NIEUWENHOVE et al (2007a;2007b), no mesmo tipo de queijo produzido com leite de búfala, e por INAYAT et al (2007) que acharam pH 5,47 em queijo de consistência mole, também produzido com leite bubalino.…”
Section: Resultsunclassified
“…Total lipids were extracted from the plasma using chloroform/methanol solution (2:1, v/v). They were derivated with HCl/methanol solution according to Van Nieuwenhove et al [ 15 ]. One micro liter of fatty acid methyl esters (FAMEs), dissolved in hexane, was injected into a gas chromatograph (GC, Model 6890 N, Agilent Technologies, Wilmington, Delaware, USA) equipped with a flame ionization detector (Agilent Technologies) and an automatic injector (Model 7683, Agilent Technologies, Shanghai, China) into an HP-88 capillary column (100 m × 0.25 mm × 0.20 μm, Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%